Phosphorous acid based deep eutectic solvents and methods of recovering lithium and transition metals from spent ternary lithium batteries
Patent Information
- Application Number
- CN202611358847.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
尽管DES表现出优异的浸出性能,但为了维持较高的浸出效率,通常需要高温和极长的浸出时间
(1)本发明设计的由亚磷酸和甜菜碱盐酸盐合成的深共晶溶剂能够实现从废旧三元锂电池中快速浸出并且回收锂及镍、钴、锰。该过程避免了高温、高能耗以及强酸、强碱或挥发性有机溶剂的使用,能够在相对温和的条件下高效浸出,具有能耗低、环境效益高的优势。
Smart Images

Figure CN122918352A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of waste ternary lithium battery recycling technology, specifically relating to a deep eutectic solvent based on phosphorous acid and a method for recovering lithium and transition metals from waste ternary lithium batteries. Background Technology
[0002] Lithium-ion batteries, with their superior performance characterized by high energy density, long cycle life, and low self-discharge rate, have deeply penetrated all aspects of modern society. Their applications range from electronic devices to transportation electrification and large-scale energy storage systems, making them an indispensable pillar in driving global energy transition and information technology advancement. However, with the exponential growth in their production and sales, the number of waste batteries has also increased dramatically, making their disposal a major environmental and resource issue that urgently needs to be addressed. Improper disposal of waste lithium-ion batteries can lead to long-term pollution of soil and water sources, resulting in ecological risks and safety hazards. Therefore, recycling waste lithium-ion batteries is urgently needed.
[0003] Furthermore, from a resource recycling perspective, the concentrations of metals such as manganese (Mn), nickel (Ni), cobalt (Co), and lithium (Li) in the cathode materials of lithium-ion batteries (LIBs) are far higher than in the original ore. Therefore, current methods for handling end-of-life lithium-ion batteries are gradually shifting towards a green circular economy model based on closed-loop recycling strategies. This primarily involves recovering valuable metals through efficient and clean recycling technologies such as physical crushing, pyrometallurgy, or hydrometallurgy. Compared to pyrometallurgy, hydrometallurgy offers numerous advantages, avoiding the large emissions of toxic gases produced under the high temperature and pressure conditions of pyrometallurgy, and featuring low energy consumption and high resource utilization. However, hydrometallurgy still faces many challenges, such as lengthy process flows, low production efficiency, high equipment investment and maintenance costs, and immense pressure in treating wastewater. These challenges provide a strong impetus for further research into more environmentally sustainable methods.
[0004] In recent years, deep eutectic solvents (DES) have attracted widespread attention as a novel, green, and efficient method for recovering valuable metals such as Mn, Ni, Co, and Li from lithium-ion oxide (LIBs). Compared with traditional pyrometallurgical and hydrometallurgical processes, this method avoids the high energy consumption problem of pyrometallurgical processes and overcomes the difficulty in recovering Li due to its tendency to permeate into the slag. Furthermore, it solves the wastewater pollution problem caused by the widespread use of strong acids and alkalis in hydrometallurgical processes. As a designable green solvent, DES can promote protonation through its hydrogen-bonded coordination ability, eroding the lattice of metal oxides under mild conditions, while selectively dissolving the target metal using its coordination ability. This new method offers high extraction efficiency and significantly reduces secondary pollution, providing a new pathway for the clean recovery of metal elements.
[0005] Deionized ether extractants (DES) typically use a low-melting-point solvent composed of a hydrogen bond donor (HBD) and a hydrogen bond acceptor (HBA) as the leaching agent to dissolve and leach metals such as Mn, Ni, Co, and Li under mild heating conditions. Although DES exhibits excellent leaching performance, maintaining high leaching efficiency usually requires high temperatures and extremely long leaching times. Furthermore, the use of co-extraction or the addition of precipitants in studies often complicates the separation of Li and transition metals from the DES leachate. Therefore, the key question is whether it is possible to achieve the separation and recovery of Li from other metals solely based on the unique properties of DES without adding additional reagents. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention designs a novel DES with bifunctionality and a low melting point, synthesized from betaine hydrochloride and phosphorous acid. The advantages of this DES lie in its low melting point and high adjustability. Under mild conditions of 60°C, it can be synthesized from waste cathode material Li in just 2 hours. 5.54 Ni 2.31 CoMn 4.69 O 10.98 Efficient leaching of Mn, Ni, Co and Li in (L-NCM).
[0007] To achieve the above objectives, the present invention adopts the following technical solution: (1) Preparation of DES leaching agent: Phosphorous acid and betaine hydrochloride are mixed in a molar ratio of 4:1 to 7:1 and 20wt% to 35wt% of deionized water is added as a diluent to reduce viscosity. The mixture is heated and stirred at 300 rpm for 30 min in a water bath at 60°C. The resulting transparent liquid product is a deep eutectic solvent based on phosphorous acid and is denoted as P-DES.
[0008] (2) Leaching of Li and transition metals: Waste ternary lithium battery cathode powder and P-DES were mixed evenly at a solid-liquid ratio of 15 g / L to 30 g / L. The mixture was placed in a water bath and heated for leaching at a stirring speed of 400 rpm for 90 to 150 min at a heating temperature of 50 to 80 °C. After leaching, the mixture was filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. The concentration of metal ions was determined by ICP-MS, and the leaching rates of Mn, Ni, Co and Li were calculated using the following equation (1): η y =[( C k × V e ) / ( m t × ωs )]×100% (1) Among them, C k Indicates the concentration (g / L) of Mn, Ni, Co, and Li in the leachate; V e Indicates the volume of the leachate (L); m t This indicates the mass (g) of L-NCM cathode powder added; ω s This indicates the mass fraction (%) of Mn, Ni, Co, and Li in the L-NCM cathode powder.
[0009] (3) Recovery of Li and transition metals: The pH of the leachate was adjusted with ammonia, and then the solution was heated and stirred in a water bath at a certain temperature for a certain time to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated sodium carbonate solution was added and heated at 95°C for 90 minutes to obtain lithium carbonate.
[0010] The pH of the leachate is adjusted within the range of 5.5 to 6.5, the temperature is adjusted within the range of 40 to 50℃, and the time is controlled within the range of 90 to 150 minutes.
[0011] This invention presents a novel deep eutectic solvent synthesized from phosphorous acid and betaine hydrochloride, which can efficiently recover Li and other transition metals from spent ternary lithium battery cathode materials under relatively mild conditions. The H₂ produced by the dissociation of phosphorous acid in the leachate... + It provides acidity and reducing power, accelerating the dissolution and reduction of Mn, Ni, Co, and Li in the cathode materials of spent ternary lithium batteries. Meanwhile, BeCl provides Cl... - The transition metals were recovered by forming metal ion crystals with Mn, Ni, and Co through coordination. Finally, the polarity of the solution was altered by adjusting the pH of the leachate. Since Li has higher solubility in the leachate than Mn, Ni, and Co, these three metals were recovered as a co-precipitate of phosphite. Subsequently, Li was recovered as sodium carbonate.
[0012] The beneficial effects of this invention are as follows: (1) The deep eutectic solvent synthesized from phosphorous acid and betaine hydrochloride designed in this invention can rapidly leach and recover lithium, nickel, cobalt and manganese from waste ternary lithium batteries. This process avoids high temperature, high energy consumption and the use of strong acid, strong alkali or volatile organic solvents, and can leach efficiently under relatively mild conditions, with the advantages of low energy consumption and high environmental benefits.
[0013] (2) The recycling process proposed in this invention effectively overcomes the difficulty of separating lithium from transition metals such as nickel, cobalt, and manganese, and achieves selective recovery of lithium. In the recycling process, the co-precipitation method is used to recover manganese, nickel, and cobalt, which simplifies the process flow and reduces the loss of valuable metals.
[0014] (3) The present invention recovers high-purity metal products by simply adding ammonia to adjust the pH value of the leachate and changing the polarity environment of the solution. No precipitant is used in the recovery process, thus avoiding the generation of inorganic salt precipitants and saline wastewater. Attached Figure Description
[0015] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation
[0016] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification. Example 1
[0017] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 4:1, and 20 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, waste ternary lithium battery cathode powder (30 wt% manganese, 18 wt% nickel, 11% cobalt, and 9% lithium) and P-DES were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a water bath at 50°C for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a water bath at 40°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain a manganese-nickel-cobalt phosphite coprecipitate and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 80.23%, 90.45%, 83.71%, and 86.59%, respectively. Example 2
[0018] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 20 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, waste ternary lithium battery cathode powder and P-DES were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a water bath at 50°C for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a water bath at 40°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain the manganese-nickel-cobalt phosphite coprecipitate and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 91.58%, 96.47%, 92.91%, and 94.45%, respectively. Example 3
[0019] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 6:1, and 20 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a 50°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 91.37%, 92.48%, 84.22%, and 88.53%, respectively. Example 4
[0020] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 7:1, and 20 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a 50°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 72.65%, 78.38%, 73.45%, and 81.23%, respectively. Example 5
[0021] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 25 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a water bath at 50°C for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a water bath at 40°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 92.45%, 96.48%, 92.76%, and 96.09%, respectively. Example 6
[0022] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a 50°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 93.23%, 96.49%, 91.35%, and 98.79%, respectively. Example 7
[0023] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 35 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 15 g / L, and heated and stirred in a water bath at 50°C for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a water bath at 40°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 85.71%, 89.99%, 83.49%, and 94.22%, respectively. Example 8
[0024] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a 50°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 92.52%, 96.46%, 91.62%, and 98.31%, respectively. Example 9
[0025] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 25 g / L, and heated and stirred in a 50°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 92.47%, 95.75%, 89.54%, and 97.55%, respectively. Example 10
[0026] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 30 g / L, and heated and stirred in a 50°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 91.98%, 93.60%, 87.64%, and 96.51%, respectively. Example 11
[0027] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a 60°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 92.89%, 96.58%, 92.04%, and 98.73%, respectively. Example 12
[0028] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a water bath at 70°C for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a water bath at 40°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 92.93%, 97.24%, 92.39%, and 98.69%, respectively. Example 13
[0029] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 90 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 93.03%, 97.31%, 92.89%, and 98.99%, respectively. Example 14
[0030] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a water bath at 80°C for 120 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a water bath at 40°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 93.91%, 97.99%, 93.29%, and 98.98%, respectively. Example 15
[0031] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 5.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 93.93%, 97.98%, 93.44%, and 98.99%, respectively. Example 16
[0032] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 93.95%, 97.97%, 93.99%, and 98.99%, respectively. Example 17
[0033] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 6.5 with ammonia. The leachate was then heated and stirred in a 40°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 88.71%, 95.29%, 89.23%, and 96.21%, respectively. Example 18
[0034] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a 45°C water bath for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 95.31%, 97.99%, 94.61%, and 98.98%, respectively. Example 19
[0035] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a water bath at 80°C for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a water bath at 50°C for 90 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 92.41%, 95.65%, 93.61%, and 98.16%, respectively. Example 20
[0036] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a water bath at 80°C for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a water bath at 45°C for 150 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 90.23%, 97.12%, 95.25%, and 97.62%, respectively. Example 21
[0037] Phosphorous acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% of deionized water (based on the total mass of phosphorous acid and betaine hydrochloride) was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a water bath at 80°C for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a water bath at 45°C for 120 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recovery rates of Li, Mn, Ni, and Co were calculated to be 96.54%, 99.94%, 98.25%, and 99.14%, respectively. Comparative Example 1
[0038] Phosphorous acid was used alone as DES, and 30 wt% deionized water was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a pure leachate. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a 45°C water bath for 120 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, the recoveries of Li, Mn, Ni, and Co were calculated to be 62.88%, 78.45%, 66.79%, and 84.23%, respectively. Comparative Example 2
[0039] Phosphorous acid and hydroxylamine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% deionized water was added. The mixture was heated and stirred in a water bath at 60°C for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in a water bath at 80°C for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a water bath at 45°C for 120 min to form a manganese-nickel-cobalt complex precipitate. The precipitate was separated by filtration to obtain manganese-nickel-cobalt phosphite and a lithium-containing solution. The pH of the lithium-containing solution was adjusted to 11, and saturated Na₂CO₃ solution was added. The mixture was heated and stirred at 95°C for 90 min to obtain Li₂CO₃. Finally, calculations showed that the recoveries of Li, Mn, Ni, and Co were 61.63%, 64.65%, 57.65%, and 68.79%, respectively. Comparative Example 3
[0040] Lactic acid and betaine hydrochloride were mixed at a molar ratio of 5:1, and 30 wt% deionized water was added. The mixture was heated and stirred in a 60°C water bath for 30 min to form P-DES. Subsequently, P-DES and spent ternary lithium battery cathode powder were placed in a glass container at a solid-liquid ratio of 20 g / L, and heated and stirred in an 80°C water bath for 150 min. The mixture was then filtered through 0.45 μm PTFE filter paper to obtain a leachate free of impurities. After leaching, the pH of the leachate was adjusted to 6 with ammonia. The leachate was then heated and stirred in a 45°C water bath for 120 min. It was found that no manganese-nickel-cobalt complex precipitate could form, proving that using lactic acid as a hydrogen bond donor could not recover Li, Mn, Ni, and Co from spent ternary lithium battery cathode materials using the route designed in this invention.
[0041] It should be noted that the above embodiments are merely illustrative and should not be considered as limiting the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should be able to recognize that various modifications or equivalent substitutions can be made without departing from the core spirit and scope of the present invention, and all resulting technical solutions should be included within the scope of the claims of the present invention.
Claims
1. A deep eutectic solvent based on phosphorous acid, characterized in that, The deep eutectic solvent is obtained by heating and stirring phosphorous acid and betaine hydrochloride.
2. The deep eutectic solvent based on phosphorous acid as described in claim 1, characterized in that, The deep eutectic solvent is prepared by mixing phosphorous acid and betaine hydrochloride, adding deionized water as a diluent, heating and stirring in a water bath to obtain a transparent and clear deep eutectic solvent.
3. The deep eutectic solvent based on phosphorous acid as described in claim 2, characterized in that, The molar ratio of phosphorous acid to betaine hydrochloride is 4–7:1; the amount of deionized water added is 20–35 wt% of the total mass of phosphorous acid and betaine hydrochloride.
4. An application of a deep eutectic solvent based on phosphorous acid as described in claim 1, characterized in that, The deep eutectic solvent is used to recover lithium and transition metals from spent ternary lithium batteries.
5. The application of the deep eutectic solvent based on phosphorous acid as described in claim 4, characterized in that, The steps for using the deep eutectic solvent to recover lithium and transition metals from spent ternary lithium batteries are as follows: (1) The waste ternary lithium battery LNCM cathode powder and the phosphorous acid-based deep eutectic solvent P-DES are mixed evenly according to the solid-liquid ratio and placed in a water bath for heating and leaching reaction; after leaching, the mixture is filtered through PTFE filter paper to obtain a leaching solution free of impurities. (2) Add ammonia water to the leachate from step (1), adjust the pH value, and then heat and stir the solution in a water bath to form a manganese-nickel-cobalt complex precipitate. Filter and separate to obtain manganese-nickel-cobalt phosphite and lithium-containing solution. (3) Add ammonia water to the lithium-containing solution, adjust the pH value, add saturated sodium carbonate solution and heat to obtain lithium carbonate.
6. The application of the deep eutectic solvent based on phosphorous acid as described in claim 5, characterized in that, In step (1), the solid-liquid ratio of LNCM cathode powder and P-DES is 15-30 g / L.
7. The application of the deep eutectic solvent based on phosphorous acid as described in claim 5, characterized in that, In step (1), the temperature of the water bath heating and stirring is 50-80℃, and the time of water bath heating and stirring is 90-150min.
8. The application of the deep eutectic solvent based on phosphorous acid as described in claim 5, characterized in that, In step (2), the pH of the leachate is adjusted to 5.5 to 6.
5.
9. The application of the deep eutectic solvent based on phosphorous acid as described in claim 5, characterized in that, In step (2), the temperature of the water bath for heating and stirring is 40-50℃, and the time for heating and stirring in the water bath is 90-150 min.